Fractionation Of Proteins In Surimi Wastewater Using Membrane Filtration - Tacharatanamanee, Raweewan; Cherdrungsi, Kitti; Youravong, Wirote (2004)
Wastewater from surimi production consists of proteins and other valuable components. Proteins, caused the difficulty in wastewater treatment can be recovered by ultrafiltration and microfiltration and then can be partially purified by bulk crystallization. The results from SDS-PAGE study showed that the range of molecular weight of the soluble proteins was about 10-100 kDa. Ultrafiltration surimi wastewater using membrane with MWCO 100 and 300 kDa could not fractionate these proteins since most the proteins were retained in the retentate. Therefore these membrane can be used for protein concentration. Fractionation of protein from this waste was also studied by using microfiltration with the membrane at the pore size of 0.22 µm, 0.45 µm and 1 µm. The results from SDS-page showed that the protein profile in the retentate and permeate did not difference, indicating that these membranes also could not use for fractionation these types of proteins. These may be due to the narrow range of the molecular weight of these proteins.